Semi-Synthesis of Marine-Derived Ilamycin F Derivatives and Their Antitubercular Activities - Li, Jun; Liu, Zhiyong; Hong, Mingye; Sun, Changli; Zhang, Tianyu; Zhang, Hua; Ju, Jianhua; Ma, Junying (Frontiers in Chemistry, 2021)
Tuberculosis (TB) is still a global disease threatening people’s lives. With the emergence of multi-drug-resistant Mycobacterium tuberculosis (Mtb), the prevention and control of tuberculosis faces new challenges, and the burden of tuberculosis treatment is increasing among the world. Ilamycins are novel cyclopeptides with potent anti-TB activities, which have a unique target protein against M. tuberculosis and drug-resistant strains. Herein, ilamycin F, a major secondary metabolite isolated from the marine-derived mutant strain Streptomyces atratus SCSIO ZH16 ΔilaR, is used as a scaffold to semi-synthesize eighteen new ilamycin derivatives (ilamycin NJL1–NJL18, 1–18). Our study reveals that four of ilamycin NJLs (1, 6, 8 and 10) have slightly stronger anti-TB activities against Mtb H37Rv (minimum inhibitory concentration, 1.6–1.7 μM) compared with that of ilamycin F on day 14th, but obviously display more potent activities than ilamycin F on day 3rd, indicating anti-TB activities of these derivatives with fast-onset effect. In addition, cytotoxic assays showed most ilamycin NJLs with low cytotoxicity except ilamycin NJL1 (1). These findings will promote the further exploration of structure-activity relationships for ilamycins and the development of anti-TB drugs.